Efficacy and Adverse Effects of Corticosteroid Pulse Therapy in Alopecia Areata - Fatemeh Rastaghi; Roxana Kaveh; Nazafarin Yazdanpanah; Akram-Sadat Sahaf; Najmeh Ahramiyanpour (Mattioli1885, 2023)
Introduction: Alopecia areata (AA) is a non-scarring, autoimmune hair loss disorder, varying in severity from small round hairless patches to the total loss of scalp or body hair. Steroid pulse therapy outcomes for AA vary. Objective: This study aimed to review the related literature regarding the efficacy, relapse rates, side effects, and prognostic factors associated with the response to different pulse corticosteroid treatments. Methods: The terms "pulse steroid therapy AND alopecia areata" and "pulse corticosteroid therapy AND alopecia areata" were searched on PubMed and Google Scholar. Results: A total of 24 articles were assessed. There was no difference in outcomes and side effects between intravenous and oral pulse corticosteroid therapy. The relapse rate and efficacy depended on the time of AA onset, age, and type: improved outcomes and decreased relapse were linked with recent onset (<6 months), younger age (<10 years), and the multifocal type. Patients with a past medical history of atopy, nail pitting, or thyroid disease and those with severe forms of AA, like alopecia totalis and alopecia universalis, had the least improvement.  Conclusion: Pulse corticosteroids effectively induce hair regrowth in AA. Betamethasone seems to be the most effective agent (followed by intramuscular triamcinolone), especially in severe cases, but more side effects may accompany it. Combining this agent with other medications can reduce the dosage and side effects. Pulses of prednisolone and methylprednisolone are less effective but safer, as they have low relapse rates and adverse effects. A combination of them with other drugs can increase their efficacy.